Therapeutic aquatic exercise in the treatment of low back pain: a systematic review - Waller, Benjamin; Lambeck, Johan; Daly, Daniel (Clinical rehabilitation, 2009)
Objective: To examine the effectiveness of therapeutic aquatic exercise in the treatment of low back pain. Design: A systematic review. Methods: A search was performed of PEDro, CINAHL (ovid), PUBMED, Cochrane Controlled Trials Register and SPORTDiscus databases to identify relevant studies published between 1990 and 2007. Population: Adults suffering from low back pain. Intervention: All types of therapeutic aquatic exercise. Comparison: All clinical trials using a control group. Outcomes: Oswestry Disability Index, McGill Pain Questionnaire, subjective assessment scale for pain (e.g. visual analogue scale) and number of work days lost as a direct result of low back pain. Methodological quality was assessed using the PEDro scale and the SIGN 50 assessment forms. Results: Thirty-seven trials were found and seven were accepted into the review. Therapeutic aquatic exercise appeared to have a beneficial effect, however, no better than other interventions. Methodological quality was considered low in all included studies. The heterogeneity among studies, in numbers of subjects, symptoms durations, interventions and reporting of outcomes, precluded any extensive meta-analysis of the results. Conclusion: There was sufficient evidence to suggest that therapeutic aquatic exercise is potentially beneficial to patients suffering from chronic low back pain and pregnancy-related low back pain. There is further need for high-quality trials to substantiate the use of therapeutic aquatic exercise in a clinical setting.